RHEOLOGICAL INVESTIGATION OF RUBBER BITUMEN CONTAINING VARIOUS WAXES AS WARM MIX ADDITIVE - GERGÓ, Péter; HOLLÓ, András; GEIGER, András (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The aim of this study is to investigate the effect of various wax type warm mix additives on the rheological properties of Chemically Stabilized Rubber Bitumen (CSRB). The rubber bitumen samples were prepared by the modified wet process (HU 226481) and the bitumen tests were carried out according to the relevant standards. Two types of warm mix additives (polypropylene wax - produced by thermal cracking of polypropylene and Fischer-Tropsch wax) with different concentrations (1.0%, 3.0%, 5.0%, 7.0% by weight) were used in our research. The influence of these warm mix additives on the rheological properties was evaluated by Dynamic Shear Rheometer (DSR) test. Multiple-stress creep and recovery (MSCR) test was also used for the determination of percent recovery and non-recoverable creep compliance of wax-modified and neat asphalt rubber samples. According to the results of DSR tests the addition of the Fischer-Tropsch wax resulted a higher complex modulus (thereby stiffness) and favourable higher recovery values based on MSCR tests unlike the addition of polypropylene wax.